2022
DOI: 10.3390/genes13122310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Selection Signatures in Anqing Six-End-White Pigs Based on Resequencing Data

Abstract: As a distinguished Chinese indigenous pig breed that exhibits disease resistance and high meat quality, the Anqing six-end-white (AQ) pig represents a valuable germplasm resource for improving the quality of the pig breeding industry. In this study, 24 AQ pigs that were distantly blood-related and 6 Asian Wild Boar (AWB) were selected for 10× deep-genome resequencing. The signatures of the selection were analyzed to explore the genetic basis of their germplasm characteristics and to identify excellent germplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Ma et al identified signatures of artificial selection and loci related to intramuscular fat content and feed conversion ratio traits in Duroc Pigs [ 11 ]. In addition, a number of studies have been carried out to explore specific signatures of selection in Chinese indigenous pig breeds, including Anqing Six-End-White [ 12 , 13 ], Saba, Baoshan, Tunchang, Dingan [ 14 ], Meishan [ 15 ] and Lulai pigs [ 16 ]. Qiao et al analyzed genetic structures and mapped genomic regions affecting backfat thickness of Yunan black pigs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al identified signatures of artificial selection and loci related to intramuscular fat content and feed conversion ratio traits in Duroc Pigs [ 11 ]. In addition, a number of studies have been carried out to explore specific signatures of selection in Chinese indigenous pig breeds, including Anqing Six-End-White [ 12 , 13 ], Saba, Baoshan, Tunchang, Dingan [ 14 ], Meishan [ 15 ] and Lulai pigs [ 16 ]. Qiao et al analyzed genetic structures and mapped genomic regions affecting backfat thickness of Yunan black pigs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%